2002
DOI: 10.1210/jc.2001-010385
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate in the Treatment of Primary Hyperparathyroid-Related Osteoporosis: A 2-Year Study

Abstract: We investigated the effect of alendronate on calcium, PTH, and bone mineral density in 27 female and 5 male patients with primary hyperparathyroidism. The treatment group [n = 14; T score < or = -2.5 SD at the femoral neck (FN) or T < or = -1.0 SD plus previous nonvertebral fracture] was given alendronate 10 mg/d for 24 months. The second group (n = 18; T score > -2.5 SD at the FN) was untreated. Biochemistry was repeated at 1.5, 3, 6, 12, 18, and 24 months, and dual-energy x-ray absorptiometry at 12 and 24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 12 publications
2
51
1
5
Order By: Relevance
“…(5) Another recently published study lacked a placebocontrolled group. (6) The two best-designed studies agree with the others that alendronate is associated with an increase in lumbar spine BMD within 1 year of therapy. Alendronate does not seem to alter significantly the serum calcium or parathyroid hormone concentration.…”
supporting
confidence: 63%
“…(5) Another recently published study lacked a placebocontrolled group. (6) The two best-designed studies agree with the others that alendronate is associated with an increase in lumbar spine BMD within 1 year of therapy. Alendronate does not seem to alter significantly the serum calcium or parathyroid hormone concentration.…”
supporting
confidence: 63%
“…In most reports, the effects of aminobisphosphonates were evident in any age, across genders, and in patients with or without previous fractures [16][17][18]. Moreover, bisphosphonates were also effective in secondary osteoporosis, such as primary hyperparathyroidism, GIO, and hypogonadism [13,[19][20][21][22][23][24][25]. Alendronate is one of the first-line drugs for the preservation and treatment of GIO with extensive evidence [13,[19][20][21]25].…”
Section: Introductionmentioning
confidence: 99%
“…38 Alendronate has been more extensively studied and either a small effect on serum calcium 39,40 or no change at all have been reported. 41,42 Within a similar context, PTH was reported either to increase 39,42,43 or to remain unchanged. 40 A multicenter, double-blind, randomized, placebo-controlled study reported no effect of alendronate on either serum calcium or PTH levels.…”
Section: Bisphosphonatesmentioning
confidence: 94%
“…The increase in bone mineral density has been a consistent finding of all studies using alendronate. [39][40][41] Similarly, risedronate reduced fasting serum calcium concentrations and biochemical markers of bone turnover in a small series of patients with primary HPT; additional studies are required to evaluate the long-term efficacy of this bisphosphonate in HPT. 37,45 The use of intravenous bisphosphonates (pamidronate, zoledronate) in primary HPT is restricted to the treatment of acute hypercalcaemia, 33 as it occurs, for example, in parathyroid crisis, which is associated with serum calcium concentrations greater than 15 mg/dl (3.75 mmol/l) and rapid deterioration of central nervous system, cardiac, gastrointestinal and renal function.…”
Section: Bisphosphonatesmentioning
confidence: 99%